Enhancing infection prevention and control through hand hygiene compliance in six Ugandan hospitals using quality improvement approaches - Kasujja, Hassan; Waswa, J. P.; Kiggundu, Reuben; Murungi, Marion; Kwikiriza, Grace; Bahatungire, Rony; Kajumbula, Henry; Alombah, Fozo; Joshi, Mohan P.; Konduri, Niranjan (Frontiers in Public Health, 2024)
Hand hygiene (HH) plays a crucial role in mitigating healthcare-associated infections. Improving HH compliance in healthcare facilities in resource-limited settings is urgently needed. We implemented the World Health Organization (WHO) HH improvement strategy using a continuous quality improvement (CQI) approach targeting improvement in HH compliance by healthcare workers (HCWs). An intervention was implemented in six hospitals using a longitudinal study design between May 2019 and April 2023. We set up and monitored infection prevention and control (IPC) and HH programs using WHO's infection prevention and control assessment framework at the facility level (IPCAF) and hand hygiene self-assessment framework (HHSAF) tools. We implemented HH interventions using CQI techniques while targeting HCW HH knowledge and compliance with the WHO's Five Moments of HH. By the end of the intervention, IPC and HH capacity improved in all six hospitals, from a median score of 547.0 and 252.5 on IPCAF and HHSAF tools at baseline to an advanced score of 635.0 and 350.0 at endline assessment, respectively. Similarly, HCWs' HH knowledge improved in all hospitals, from a mean score of 45.0% at baseline to 76.0% at endline assessment, most notably among nurses. HH compliance, as assessed using WHO's HH observation tool, at least doubled in all hospitals, rising from 19.9% to 53.8%, with before touching a patient registering the highest (22-fold) improvement. On linear regression analysis, no significant association was observed between HH compliance and IPCAF b = -0.0004 (95% CI -0.093, 0.93) p = 0.990, HHSAF b = 0.009 (95% CI -.0127, 0.145) p = 0.842 and HCW knowledge on HH/IPC b = -0.165 (95% CI 0.815, 0.485) p = 0.519. In conclusion, implementation of the WHO HH improvement strategy using a CQI approach can lead to remarkable improvement in HH capacity, and HCW compliance and knowledge in hospitals within resource-limited settings.